Weber-Christian disease (idiopathic panniculitis): Clinical aspects - O. N. Egorova; B. S. Belov; S. I. Glukhova; S. G. Radenska-Lopovok; Yu. A. Karpova (Современная ревматология, 2016)
Weber-Christian disease (WCD), or idiopathic panniculitis, refers to rare diseases from a group of systemic connective tissue diseases. To verify the diagnosis of WCD is a difficult task, for there are no precise diagnostic tests for this disease.Objective: to study the clinical features and additional investigation data of WCD as one of the variants of lobular panniculitis (LP).Subjects and methods. Nineteen patients (2 men and 17 women) aged 32 to 71 years with WCD were examined. The average disease duration was 65.1±11.3 months.Results. The medical history data of 12 patients could identify three suspected factors of disease development: surgical intervention (n = 6); supercooling (n=4), and acute respiratory viral infection (n=2). In 10 (53%) patients aged 47–71 years, the Quetelet index was as high as 31.8±7.2 cm/kg, which allowed grade 2 obesity to be diagnosed. According to its clinical manifestations, there were 3 WCD forms: nodular (n=10), plaque (n=6), and infiltrative (n=3). The saucer symptom was present in 74%, including in all cases of the chronic course (p=0.02). The number of affected areas significantly differed in the nodular and plaque forms (p=0.01). ROC analysis showed that the optimal values of sensitivity (80%) and specificity (83%) on visual analog scale (VAS) in patients with these forms corresponded to a separation point of 60 mm, with the prognostic value of a positive result being 0.89 (CI 0.71–1.1; p=0.011). The infiltrative form showed a typical clinical picture (VAS, 83.1±12.5 mm) in 3 patients, one of them was found to have mesenteric panniculitis. The level of C-reactive protein was shown to be correlated with the form of the disease; the former being maximal in infiltrative WCD. The pathomorphological examination of skin and subcutaneous fat biopsy specimens from the nodule of all the patients detected diffuse leukolymphocytic infiltration, single multinucleated cells, necrotic foci, and lipocyte proliferation.Conclusion. WCD is a clinical variant of LP, which requires an extended diagnostic search.